2010
DOI: 10.1007/s11926-010-0114-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Life Measurements Versus Disease Activity in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic disease affecting the physical, social, and psychological well-being of patients. Different instruments have been developed to measure health-related quality of life, some of which are SLE-specific. Contributors to poor quality of life in patients with SLE include fatigue, fibromyalgia, depression, and cognitive dysfunction. Health-related quality of life is not strongly associated with disease activity or organ damage. The Medical Outcomes Survey Short Form 36 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 75 publications
(98 reference statements)
1
52
0
Order By: Relevance
“…22 Another related cause is fibromyalgia, which we did not study, which could be related to quality of life and fatigue. 23 The lack of data on other factors like fibromyalgia, anemia and thyroid functions is a limitation of this study. The higher fatigue (lower FACIT-F score) in patients on higher doses on oral steroids is interesting and may due to a direct effect of chronic high-dose steroids or it may indicate residual disease activity.…”
Section: Discussionmentioning
confidence: 91%
“…22 Another related cause is fibromyalgia, which we did not study, which could be related to quality of life and fatigue. 23 The lack of data on other factors like fibromyalgia, anemia and thyroid functions is a limitation of this study. The higher fatigue (lower FACIT-F score) in patients on higher doses on oral steroids is interesting and may due to a direct effect of chronic high-dose steroids or it may indicate residual disease activity.…”
Section: Discussionmentioning
confidence: 91%
“…HRQoL is compromised in SLE patients as a result of the disease itself but frequently also due to the coexistence of aggravating factors, especially fatigue, pain and depression (reviewed in62 63). Thus, cross-sectional studies have reported weak inverse associations between HRQoL and measures of SLE activity64–66 and damage64 65 67–69 (correlation coefficients typically in the range of −0.20 to −0.52).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also suggested that disease activity has an impact on HRQoL. 9,10 The prevalence of fatigue among patients with SLE is high and is present in up to 90% of patients. 18 In this study, the mean value of fatigue among all SLE patients was 6.1, comparable to results from other studies including patients with SLE.…”
Section: Discussionmentioning
confidence: 99%